Consider the differential equation: (y^2+2*x)dx+(2*x*y-1)dy = 0. (a) show that the equation is exact by evaluating (\partial m)/(\partial y) = (\partial n)/(\partial x)= (b) determine the general solution in implicit form: incorrect: your answer is incorrect. = c

Respuesta :

The given ODE

[tex]\underbrace{(y^2+2x)}_M\,\mathrm dx+\underbrace{(2xy-1)}_N\,\mathrm dy=0[/tex]

is exact if [tex]\frac{\partial M}{\partial y}=\frac{\partial N}{\partial x}[/tex]. It so happens that we have [tex]\frac{\partial M}{\partial y}=2y=\frac{\partial N}{\partial x}[/tex], so it is indeed exact. For such an ODE, we're looking for a solution of the form [tex]\Psi(x,y)=C[/tex], for which the differential is

[tex]\mathrm d\Psi=\dfrac{\partial\Psi}{\partial x}\,\mathrm dx+\dfrac{\partial\Psi}{\partial y}\,\mathrm dy=0[/tex]

so we have the following system of PDEs that allow us to solve for [tex]\Psi[/tex]:

[tex]\dfrac{\partial\Psi}{\partial x}=M=y^2+2x[/tex]

[tex]\dfrac{\partial\Psi}{\partial y}=N=2xy-1[/tex]

In the first PDE, we can integrate both sides with respect to [tex]x[/tex] and recover [tex]\Psi[/tex]:

[tex]\displaystyle\int\frac{\partial\Psi}{\partial x}\,\mathrm dx=\int(y^2+2x)\,\mathrm dx[/tex]

[tex]\implies\Psi(x,y)=xy^2+x^2+f(y)[/tex]

Then differentiating this with respect to [tex]y[/tex] returns [tex]N[/tex]:

[tex]\dfrac{\partial\Psi}{\partial y}=2xy+\dfrac{\mathrm df}{\mathrm dy}=2xy-1[/tex]

[tex]\implies\dfrac{\mathrm df}{\mathrm dy}=-1[/tex]

[tex]\implies f(y)=-y+C[/tex]

So the general solution to the ODE is

[tex]\Psi(x,y)=xy^2+x^2-y+C=C[/tex]

or simply

[tex]xy^2+x^2-y=C[/tex]

ACCESS MORE